Processing, products, and food safety: Trimming and washing poultry carcass to reduce microbial contamination: A comparative study - Backes R.G.* (2014)
© 2014 Poultry Science Association Inc.The objective of this study was to compare the efficiency of washing and trimming broiler carcasses to reduce bacterial contamination. At the postevisceration site, 100 broiler carcasses were collected during 4 visits to a slaughterhouse in Santa Catarina State, Brazil. Birds were from the same flock, age, and approximately 2.4 kg of weight. Groups were as follows: group 1, with fecal contamination; group 2, without fecal contamination; group 3, with fecal contamination and trimmed; group 4, with fecal contamination and washed; group 5, with fecal contamination, and washed and trimmed. Carcass washings were performed with at least 1.5 L/bird of potable water (0.5 to 1 mg/kg of residual chlorine) at room temperature (20-25°C) using spray cabinets with 44 spray nozzles distributed into 2 chambers (pressure of 2 kgf/cm2 and 4 kgf/cm2). Washed carcasses (trimmed or not) showed significantly (P < 0.05) lower counts of aerobic mesophiles (plate count agar) on the third evaluation, and even lower (P < 0.01) counts for total coliforms (CT) and fecal coliforms (Escherichia coli). Trimmed carcasses showed significantly lower counts (P < 0.05) for plate count agar; however, we observed higher counts for E. coli (P < 0.05). The association of both treatments (washing and trimming) showed significantly higher (P < 0.05) counts for coliforms (CT and E. coli). We can conclude that the washing method is overall more efficient than the trimming method to decontaminate chicken carcasses at the postevisceration site. Hopefully, our findings can help poultry companies to minimize production costs by applying the washing method for carcass decontamination.